2021
DOI: 10.1002/agg2.20197
|View full text |Cite
|
Sign up to set email alerts
|

Biochar affects soil water content but not soybean yield in a sandy southeastern U.S. soil

Abstract: Drought is the greatest abiotic cause of soybean [Glycine max (L.) Merr.] yield loss in rainfed systems in the United States. Preplant incorporation of powdery biochar to soil cultivated with soybean in these water-stressed regions presents the potential to increase volumetric soil water content (VSWC) between rainfall events and ameliorate the impact of intermittent water stress. However, VSWC and the aboveand belowground response of soybean to biochar amendment are not well understood. This 2-yr field study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…They also found that the SWS was positively linked with the biochar application rate, as demonstrated in numerous studies [45,46]. Possible reasons for the increment in SWS are the reduction in soil bulk density and improvement in soil aggregate after biochar addition, which facilitates the soils in retaining more water [43].…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 78%
See 1 more Smart Citation
“…They also found that the SWS was positively linked with the biochar application rate, as demonstrated in numerous studies [45,46]. Possible reasons for the increment in SWS are the reduction in soil bulk density and improvement in soil aggregate after biochar addition, which facilitates the soils in retaining more water [43].…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 78%
“…Our findings are consistent with those of Razzaghi et al [42], whose global-scale meta-analysis on the effects of biochar incorporation on soil moisture retention indicated a notable augmentation in the water retention capacity of the treated soils that was particularly discernible in soils characterized by coarse textures. Additionally, the clay and silt contents are important factors that can interact with biochar to form a soil matrix, resulting in increased water-holding capacity [43]. Moreover, higher biochar application rates may be needed for soils characterized by high sand content to achieve an equivalent effect.…”
Section: Soil Physicochemical Propertiesmentioning
confidence: 99%